Nutritional therapy in patients with Chronic Kidney Disease: Narrative review (Research, Society and Development, 2021)
Research on nutritional therapy in chronic kidney disease. This is an integrative literature review, through a systematic search with the terms described in the DeSC (Nutritional Therapy, Patient Care, Chronic Kidney Failure) through the combination of them, using the Boolean operators (AND, OR , AND NOT), this search was carried out through a vast research with studies from the last 19 years, in the databases Pubmed, Scielo and Periódico Capes, all texts that were found relevant to the study were used, were excluded from the articles that they were not open access and those that did not deal with the theme. Renal filtration is the main and best-known function of the kidneys, being carried out by the process of ultrafiltration and glomerular reabsorption. Ultrafiltration occurs with the selective transfer of ions, molecules and water through the capillaries that form the glomerulus, in a space in the nephron known as the Bowman's capsule, in contrast the reabsorption results from the passage of substances outside the nephron tubule, of the interstice or to the renal capillaries. According to the study, it was observed that patients with chronic kidney disease on hemodialysis are a vulnerable public, requiring constant monitoring of nutritional status as it is a strong predictor of morbidities and mortality.